Cell-cycle-independent transitions in temporal identity of mammalian neural progenitor cells - Mayumi Okamoto (Nature Portfolio, 2016)
The molecular mechanisms determining the temporal identity patterns of self-renewing progenitors during cerebral development are largely unclear. Here, using single cell transcriptome analyses, the authors find progenitor temporal identity arises independent of cell-cycle progression and Notch activation.